2017
DOI: 10.1186/s12879-017-2264-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods for identifying causative bacterial microorganisms in presumed acute endophthalmitis: conventional culture, blood culture, and PCR

Abstract: BackgroundIdentification of bacterial pathogens in endophthalmitis is important to inform antibiotic selection and treatment decisions. Hemoculture bottles and polymerase chain reaction (PCR) analysis have been proposed to offer good detection sensitivity. This study compared the sensitivity and accuracy of a blood culture system, a PCR approach, and conventional culture methods for identification of causative bacteria in cases of acute endophthalmitis.MethodsTwenty-nine patients with a diagnosis of presumed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 25 publications
0
31
0
2
Order By: Relevance
“…In one of our previous study, the bacterial detection using conventional and automated culture in endophthalmitis was 13.33% vs 33.33%, respectively 18. In other studies the bacterial detection rate by conventional and automated culture was 12.2% (5/41) vs 26.8% (11/41) from Thailand,2 16.8% (81/483) vs 31.1% (150/483) from Chennai, India,4 33% (47/140) vs 55% (77/140) from the UK,19 35% (14/40) vs 65% (26/40) from Tehran17 and 53.9% (7/13) vs 69.2% (9/13) from Israel,3 respectively. Since a significant increase in the isolation rate of bacteria occurs using automated culture method, wherever molecular methods are not feasible automated culture method should be ideally used for microbial diagnosis of endophthalmitis.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In one of our previous study, the bacterial detection using conventional and automated culture in endophthalmitis was 13.33% vs 33.33%, respectively 18. In other studies the bacterial detection rate by conventional and automated culture was 12.2% (5/41) vs 26.8% (11/41) from Thailand,2 16.8% (81/483) vs 31.1% (150/483) from Chennai, India,4 33% (47/140) vs 55% (77/140) from the UK,19 35% (14/40) vs 65% (26/40) from Tehran17 and 53.9% (7/13) vs 69.2% (9/13) from Israel,3 respectively. Since a significant increase in the isolation rate of bacteria occurs using automated culture method, wherever molecular methods are not feasible automated culture method should be ideally used for microbial diagnosis of endophthalmitis.…”
Section: Discussionmentioning
confidence: 78%
“…Other studies have found CoNS are the most common bacteria among all detected pathogens: 44% (23/50) from Hyderabad (India),23 17.34% (17/98) from Chennai (India),23 17.6% (6/34) from Turkey,2 48% (17/97) from Brazil2 and 70% from the USA 1. Among these CoNS groups, S. epidermidis was the most common bacterial species in our study, comprising 67.39% of all CoNS isolates and 24.4% of all bacteria.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Prior work shows that blood culture and PCR have a higher diagnostic yield for endophthalmitis than conventional plate culture in vitreous specimens [14], and blood culture requires a larger volume specimen than PCR. Aqueous specimens typically are smaller in volume than vitreous specimens, but obtaining an aqueous specimen is technically easier than obtaining a vitreous specimen, and a diagnostic anterior chamber paracentesis may be less likely than a vitreous tap to cause an associated retinal detachment.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of our review is that we did not plan to perform separate analyses of culture-positive and culturenegative endophthalmitis. In fact, this complication is usually diagnosed on the basis of a spectrum of clinical features including pain, decreased visual acuity, hypopyon and posterior segment inflammation, and is frequently underestimated by culture tests [52].…”
Section: Strengths and Limitations Of This Reviewmentioning
confidence: 99%